The Effectiveness of Talking Chips Model Aided by Visual Media Toward Javanesse Language Learning Outcomes - Sutaryono, Sutaryono (Journal of Research and Educational Research Evaluation, 2019)
Based on the results of observation, interview, and the data of learning outcomes, it was obtained that Javanesse language learning outcomes was less maximal, the model used by teacher was unvaried, and the limitation of the media used. This research aimed to examine the effectiveness of talking chips model aided by visual-media towards Javanesse language learning outcomes on fifth grade students of Gugus Cendana Elementary School, Blora Regency. This research used experimental quantitative method focused on nonequivalent control group design. The technique for choosing the sample was cluster random sampling. The total sample used in this research was 36 students. The method of collecting the data was by giving test, observation, interview, and documentation. The result of hypothesis test showed that the score of t count=3.067, and t table= 2.032, t count > t table (3.067 > 2.032), it meant that talking chips model aided by visual-media more effective for the Javanesse language learning outcomes. The result of n-gain on experimental group was higher than the controlled one. The score of n-gain on controlled group was 0.029 which belonged to the low level. Whereas, the score of n-gain on experimental group was 0.52 which belonged to the medium level. The result of observation on students’ activity showed that the score average of experimental group was higher than the controlled one. While the experimental group stood for 76.5%, the controlled group stood for 62%. The conclusion of this research pointed out that talking chips model aided by visual-media was effective for the Javanesse language learning outcomes on the fifth grade students of Gugus Cendana Elementary School, Blora Regency. In this case, the researcher suggest that talking chips model aided by visual-media can be used as an alternative of learning model which can be applied to enhance the students’ activity, giving the same chance for the students in the learning process. Therefore, hopefully the teacher is able to create an interesting and wonderful learning atmosphere for the students; so that the students are able to achieve the learning objectives.